2020
DOI: 10.1002/col.22542
|View full text |Cite
|
Sign up to set email alerts
|

Recovering figure‐ground perception in Tehran's color plan

Abstract: Tehran's color plan was carried out during 1990s with the primary purpose of restoring color consistency particularly to the historic center of the city. In fact, it attempted to bring unity and avoid color pollution to the cityscape. However, it seems to have been neglectful of many other factors, including orientation, legibility, and the mental image of the city. Further analysis shows that it fails to address figure-ground perception, as a sign of hierarchy and order, on the urban scale. Hence, this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Colour changes citizens' understanding of an urban space. Through its ability to change the emotional attachment between citizens and urban forms, colour can be a powerful tool for integrating urban style 58 . We found that the main colours of the traditional buildings in the Hubushan historical preservation area of Xuzhou are consistent with the main colours of the new buildings, and the houses and other buildings of the Ming and Qing Dynasties are well preserved (Figure 22).…”
Section: Resultsmentioning
confidence: 77%
“…Colour changes citizens' understanding of an urban space. Through its ability to change the emotional attachment between citizens and urban forms, colour can be a powerful tool for integrating urban style 58 . We found that the main colours of the traditional buildings in the Hubushan historical preservation area of Xuzhou are consistent with the main colours of the new buildings, and the houses and other buildings of the Ming and Qing Dynasties are well preserved (Figure 22).…”
Section: Resultsmentioning
confidence: 77%